Thermal output analysis of a designed parabolic trough solar field for moderate temperature industrial load - Masood, R. (Engg Journals Publications, 2016)
This paper presents an overview of the Parabolic Trough Solar Collectors, which is a fastest growing technology amongst concentrated solar power technologies. It is largely being used in developed countries; mainly in steam power cycles for electricity generation but its use is not limited to electric power generation. This technology is also being used for many other applications like refrigeration and air-conditioning, desalination of sea water, pumping of irrigation water and many other heating applications for process industry. Though this technology is already being used in many developed countries but there is barely any development in Malaysia. There is thus need for assessment of this technology to explore the potential industrial applications, under local environmental conditions. In this article basic design and development considerations for a parabolic trough collector system have been discussed. This paper also includes a thermal output analysis of a designed parabolic trough solar field to provide the baseline information for industrial applications feasibility study. System Advisor Model (SAM) has been used for this analysis, under environmental conditions of Ipoh, Malaysia. The results of simulation indicate that considerable amount of high temperature thermal energy can be obtained. The heat transfer fluid temperature reached up to 200 to 230Â°C, which can be used to operate an unfired boiler to produce steam or in some other industrial thermal application.